ANALYSIS OF MARKETING EFFICIENCY IN THE CHIP AGROINDUSTRY IN PUTOH VILLAGE PEUSANGAN SUBDISTRICT BIREUEN REGENCY - Nur Jannah Simatupang; Suryadi; Eva Wardah; Fadli; Riani (Jurnal Mahasiswa Agribisnis, 2026)
This study aims to analyze the marketing efficiency of the chip agroindustry" Dhapue Keripik Cap Bunga Dahlia" located in Gampong Putoh, Peusangan Subdistrict, Bireuen Regency. The focus of the research includes identifying the marketing channels used, analyzing marketing margins, farmer’s share, and the level of marketing efficiency in each channel. The research employed a quantitative approach using primary data collected through interviews with the business owner and resellers, as well as secondary data from literature sources. The results showed that there are two marketing channels: (1) direct sales from producer to consumer, and (2) producer – retailer/reseller – consumer. The first channel, with no intermediaries involved, resulted in a marketing margin of zero and a farmer’s share of 100%, making it the most efficient channel. The second channel yielded a marketing margin of IDR 20,000 per kilogram and a farmer’s share ranging from 66.7% to 71.4%, which is also considered efficient as it remains below the 50% marketing efficiency threshold. Therefore, both marketing channels are considered efficient, although the direct-to-consumer channel provides higher benefits to the producer. This research is expected to serve as a reference for business owners and policymakers in improving the effectiveness of distribution and marketing strategies for local agroindustrial products.